Innovation in Learning Biotechnology through a Virtual Laboratory Based on Islamic Values in High Schools - Olivia Banati; Achmad Ali Fikri (CV. Generasi Intelektual Digital (GEN ID), 2025)
Limited laboratory facilities and suboptimal practical activities are problems in biology education, particularly in biotechnology classes in high schools. To address these issues, this study aims to develop an educational medium in the form of a virtual laboratory based on Islamic values for biotechnology material in high schools. This research and development (R&D) employed the 4D development model, which consists of four stages: define, design, develop, and disseminate. Data were analyzed using descriptive qualitative and quantitative methods. The results showed that the feasibility level, as assessed by the media validation test, reached 88%, the material expert validation test reached 90%, and the Islamic values expert validation test reached 92%, each falling into the “highly valid/highly feasible” category. The practicality test by teachers scored 84%, and the practicality test by students scored 80.3%, both categorized as “practical/feasible.” These findings indicate that the virtual laboratory based on Islamic values in biotechnology material at the high school level is considered practical and feasible for use in learning. It is expected that this virtual laboratory can serve as an innovative learning medium for teachers and students.